Is there a role for bladder preserving strategies in the treatment of muscle-invasive bladder cancer? - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
Single modality bladder sparing therapy for muscle-invasive bladder cancer, including transurethral resection, systemic chemotherapy or radiotherapy have been demonstrated to result in insufficient local control of the primary tumor as well as decreased long-term survival of the patients when compared to radical cystectomy. Therefore, multimodality treatment protocols that aim at bladder preservation and involve all of the aforementioned approaches have been established. Arguments for combining systemic chemotherapy with radiation are to sensitize tumor tissue to radiotherapy and to eradicate occult metastases that have already developed in as many as 50% of patients at the time of first diagnosis. It has been shown that the clinical outcome observed with this approach approximates that after radical cystectomy. Additionally, a substantial number of patients survive with an intact bladder. However, bladder preserving approaches are costly, and require close co-operation between different clinical specialists as well as very close follow-up. The good long-term results obtained after cystectomy and creation of an orthotopic neobladder make the possible advantage of a bladder preservation strategy questionable in consideration of quality of life issues. Additionally, side effects related to bladder sparing therapy may result in an increased morbidity and mortality in those patients who in fact need to undergo surgery due to recurrent or progressive disease. Multimodality bladder sparing treatment is a therapeutic option that can be offered to the patient at centres that have a dedicated multidisciplinary team at their disposal. However, radical cystectomy remains the standard of care for muscle-invasive bladder tumors. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: bladder cancer; radical cystectomy; bladder sparing treatment; TRANSITIONAL-CELL-CARCINOMA; 5-YEAR FOLLOW-UP; SPARING RADICAL CYSTOPROSTATECTOMY; SELECTIVE ORGAN PRESERVATION; 2ND TRANSURETHRAL RESECTION; COMBINED-MODALITY THERAPY; QUALITY-OF-LIFE; RADIATION-THERAPY; NEOADJUVANT CHEMOTHERAPY; CISPLATIN CHEMOTHERAPY